1913
DOI: 10.1084/jem.18.1.107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hematin on the Circulation and Respiration

Abstract: 1. Doses of less than six milligrams of hematin and, under certain conditions, larger doses may cause a slight rise of blood pressure. 2. Large doses of hematin cause a profound and prolonged fall of blood pressure. The principal factor in this fall of blood pressure is the marked dilatation of the splanchnic vessels. The splanchnic dilatation either does not occur at all or but very slightly if the splanchnic nerves are cut. The splanchnic dilatation is partly compensated for by a marked constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1942
1942
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In 1912 Brown and co-workers (353)(354)(355)(356) found that intravenous injections of alkaline hematin solutions into rabbits caused a paroxysm similar to that observed in malaria, and concluded that hematin was the cause of the malarial paroxysms. They found also similar changes in the blood picture and effects on the vascular system, i.e., vasoconstriction followed by vasodilation.…”
Section: Toxicity Of Hematinmentioning
confidence: 97%
“…In 1912 Brown and co-workers (353)(354)(355)(356) found that intravenous injections of alkaline hematin solutions into rabbits caused a paroxysm similar to that observed in malaria, and concluded that hematin was the cause of the malarial paroxysms. They found also similar changes in the blood picture and effects on the vascular system, i.e., vasoconstriction followed by vasodilation.…”
Section: Toxicity Of Hematinmentioning
confidence: 97%
“…The hematin which is liberated into the blood plasma may be a factor in causing the malarial paroxysm since Brown (1912) showed that alkaline hematin injected intravenously into experimental animals caused a similar paroxysm. He also re¬ ported (Brown 1913a(Brown , 1913bBrown and Loevenhart 1913) that hematin produced pathological changes in the blood, circula¬ tion and kidneys somewhat comparable to those seen in malignant malaria.…”
Section: Blood Pigmentsmentioning
confidence: 85%
“…The effect of malaria on the circulation is often profound, but most of the observa¬ tions on man have been purely clinical. Brown and Loevenhart (1913) found that the injection of alkaline hematin into dogs and cats caused dilatation of the splanchnic vessels, constriction of the cutaneous ves¬ sels and a marked fall in blood pressure. The heart rate was slowed and the cardiac output diminished.…”
Section: Circulationmentioning
confidence: 99%
“…Moreover, a pronounced tendency towards hemorrhage was observed in the affected and surrounding tissue [ 138 ]. In 1913, this was confirmed in cats and dogs after injection of hematin (in the range of 3.5–9 mg per kg body weight) into the viscera and the peritoneal cavity [ 140 ], as well as in rabbits, where it occurred as hemorrhagic kidney injury and/or extensive hemorrhage in the peritoneal cavity after injection of large hematin doses (10–25 mg per kg) [ 141 , 142 ]. Furthermore, W. H. Brown described the formation of hyaline thrombi or emboli in the smaller, primarily glomerular vessels and subsequent occurrence of vaso-occlusion and vascular injuries.…”
Section: Thrombotic Complications Upon Heme Injectionmentioning
confidence: 99%
“…The transition between bleeding and thrombotic events seems to be smooth, since there are also studies that report both effects in the same study (10–25 mg/kg hematin) [ 141 , 143 ]. Moreover, there are single exceptions (three studies) that also report bleeding upon administration of lower hematin (3.5–9 mg/kg) [ 140 , 162 ] or heme arginate (2–3 mg/kg) [ 168 ] concentrations.…”
Section: Figurementioning
confidence: 99%